Studying the influence of the conjugate technological stages on the performance of linear benzenes synthesis unit via the mathematical model; Petroleum and Coal; Vol. 60, iss. 1 - Dolganova I. O. Irena Olegovna; Ivanchina E. D. Emilia Dmitrievna; Ivashkina E. N. Elena Nikolaevna; Borissov A. A. Anatoli Alimpievich (2018, 2018)
Title screen